CONSUMER PREFERENCES TOWARD INSTANT FOOD PRODUCTS IN YOGYAKARTA - Antik Suprihanti (UPT Penerbitan Universitas Jember, 2012)
The change of life styles in the last decades has increased the percentage ofconsumer population that consumed instant foods. On the other side, there are manycompeting producers that sell these instant food products. Therefore, producer needsto figure out the consumers' considerations before they choose the product. Thisresearch is a very important for the marketing strategy. The objectives of this researchare to know the consumer preferences in consuming food products and to find out howthey are informed about the products. Research methods are based on survey data ofconsumer that was taken by judgement sampling method in Yogyakarta within 2011.The products researched are instant food and beverage products which are generallyconsumed, always available in many marketplaces, and also knownly branded, such asnoodle and tea and coffee. The results of this research show that majority of theconsumers choose the product because of the taste. Information about the product theyget from intense advertising in television and most of them buy the product insupermarket or minimarket. Some recommendation to the company is the marketingstrategy shall be done by making variance in taste of the product. Research about typesof taste that customer desired is very important to know customer preference. Beside,promoting through television and supply the products to the minimarket/supermarketis done continuously.